2010
DOI: 10.1089/bfm.2009.0003
|View full text |Cite
|
Sign up to set email alerts
|

Early Exclusive Breastfeeding and Maternal Attitudes Towards Infant Feeding in a Population of New Mothers in San Francisco, California

Abstract: Background: Positive parental attitudes towards infant feeding are an important component in child nutritional health. Previous studies have found that participants in the Special Supplemental Women, Infants, and Children (WIC) Program have lower breastfeeding rates and attitudes that do not contribute towards healthy infant feeding in spite of breastfeeding and nutrition education programs targeting WIC participants. The objective of this study was to assess the frequency of exclusive breastfeeding in the ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 21 publications
1
37
0
3
Order By: Relevance
“…El estudio de Rodríguez-García et al [11], halló que uno de los perjuicios más declarados por las madres fue el de molestias y dolor con el amamantamiento. Además, otra investigación en California-Estados Unidos, encuentra que la incomodidad o el dolor al lactar se asociaban con uso de leche artificial o alimentación complementaria [26].…”
Section: Discussionunclassified
“…El estudio de Rodríguez-García et al [11], halló que uno de los perjuicios más declarados por las madres fue el de molestias y dolor con el amamantamiento. Además, otra investigación en California-Estados Unidos, encuentra que la incomodidad o el dolor al lactar se asociaban con uso de leche artificial o alimentación complementaria [26].…”
Section: Discussionunclassified
“…A northern California study found that Asian and Pacific Islander women were observed to start formula or mixed feeding of their infants sooner after birth than white women. 25 Interventions to promote optimal interpregnancy intervals need to integrate breastfeeding promotion with contraceptive dispensing and counseling, in particular with the Asian and Pacific Islander population. As exclusive breastfeeding becomes more prevalent, the potential effect of delayed initiation of effective contraception has to be monitored.…”
Section: Discussionmentioning
confidence: 99%
“…While expressing awareness and knowledge about the benefits of breastfeeding for themselves and their infant, nipple pain and painful latch were frequently and forcefully identified as obstacles. [14][15][16][17][18][19][20][21][22][23] Mothers expressed misconceptions regarding low milk supply and contraindications to breastfeeding. They also articulated a general lack of knowledge about the process of breastfeeding in areas ranging from feeding frequency, nipple care, and good latch to building milk supply.…”
Section: Risk Appraisalmentioning
confidence: 99%